Establishment and evaluation of a trauma clinic based in a primary care setting - S. M. STEWART, & I. C. MACKIE (Paediatric Dentistry, 2004)
The aim of this study was to establish and evaluate a referral centre for the treatment of children with traumatized teeth in an area remote from a dental hospital.